Improving the Learning Outcomes of Class IV Students of SDN 1 Kleteran Using the Snowball Throwing Learning Model - Aulianingsih, Natri; Yulianti, Astri; Hajro, Kun Hisnan (Prosiding University Research Colloquium, 2021)
The purpose of this research was to improve students' ability to ask questions by applyingthe Snowball Throwing learning model. The research method used was Classroom ActionResearch (CAR) which consists of two cycles where each cycle has stages of planning,action, observation and reflection. Based on the results of observations and tests, in thefirst cycle there was an increase. The highest score after treatment in cycle 1 was 80 andthe lowest score was 70 with an average of 75.7. while the highest initial data was 80, thelowest value is 68 and the average is 73.3. while more significant results were found in thesecond cycle, namely the highest score of students was 86, the lowest score was 78, and theaverage was 81.9. So it can be concluded that the Snowball Throwing learning model canincrease students' interest in asking.